COVID-19–Associated Nonocclusive Fibrin Microthrombi in the Heart. Issue 3 (19th January 2021) - Bois, Melanie C.; Boire, Nicholas A.; Layman, Andrew J.; Aubry, Marie-Christine; Alexander, Mariam P.; Roden, Anja C.; Hagen, Catherine E.; Quinton, Reade A.; Larsen, Christopher; Erben, Young; Majumdar, Ramanath; Jenkins, Sarah M.; et al.
Abstract : Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its resultant clinical presentation, coronavirus disease 2019 (COVID-19), is an emergent cause of mortality worldwide. Cardiac complications secondary to this infection are common; however, the underlying mechanisms of such remain unclear. A detailed cardiac evaluation of a series of individuals with COVID-19 undergoing postmortem evaluation is provided, with 4 aims: (1) describe the pathological spectrum of the myocardium; (2) compare with an alternate viral illness; (3) investigate angiotensin-converting enzyme 2 expression; and (4) provide the first description of the cardiac findings in patients with cleared infection. Methods: Study cases were identified from institutional files and included COVID-19 (n=15: 12 active, 3 cleared), influenza A/B (n=6), and nonvirally mediated deaths (n=6). Salient information was abstracted from the medical record. Light microscopic findings were recorded. An angiotensin-converting enzyme 2 immunohistochemical H-score was compared across cases. Viral detection encompassed SARS-CoV-2 immunohistochemistry, ultrastructural examination, and droplet digital polymerase chain reaction. Results: Male sex was more common in the COVID-19 group ( P =0.05). Nonocclusive fibrin microthrombi (without ischemic injury) were identified in 16 cases (12 COVID-19, 2 influenza, and 2 controls) and were more common in the active COVID-19 cohort ( P =0.006). Four active COVID-19 cases showed focal myocarditis, whereas 1 case of cleared COVID-19 showed extensive disease. Arteriolar angiotensin-converting enzyme 2 endothelial expression was lower in COVID-19 cases than in controls ( P =0.004). Angiotensin-converting enzyme 2 myocardial expression did not differ by disease category, sex, age, or number of patient comorbidities ( P =0.69, P =1.00, P =0.46, P =0.65, respectively). SARS-CoV-2 immunohistochemistry showed nonspecific staining, whereas ultrastructural examination and droplet digital polymerase chain reaction were negative for viral presence. Four patients (26.7%) with COVID-19 had underlying cardiac amyloidosis. Cases with cleared infection had variable presentations. Conclusions: This detailed histopathologic, immunohistochemical, ultrastructural, and molecular cardiac series showed no definitive evidence of direct myocardial infection. COVID-19 cases frequently have cardiac fibrin microthrombi, without universal acute ischemic injury. Moreover, myocarditis is present in 33.3% of patients with active and cleared COVID-19 but is usually limited in extent. Histological features of resolved infection are variable. Cardiac amyloidosis may be an additional risk factor for severe disease. Abstract : Supplemental Digital Content is available in the text.